2017
DOI: 10.3390/molecules22081305
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Functions of Snake Venom Metalloproteinases (SVMP) from Protobothrops venom Collected in Japan

Abstract: Snake venom metalloproteinases (SVMP) are widely distributed among the venoms of Crotalinae and Viperidae, and are organized into three classes (P-I, P-II and P-III) according to their size and domain structure. P-I SVMP are the smallest SVMP, as they only have a metalloproteinase (M) domain. P-II SVMP contain a disintegrin-like (D) domain, which is connected by a short spacer region to the carboxyl terminus of the M domain. P-III SVMP contain a cysteine-rich (C) domain, which is attached to the carboxyl termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The main compound of the fraction 4 is the svMP-i pEKW, while the pEQW containing fraction 7/8 is similarly potent. According to these results, the P. flavoviridis venom, svMP-is, exhibits remarkable effects on SH-SY5Y cells, while, until now, only the correlating svMP of most Protobothrops venoms were known to have an important role in envenomation-related pathologies [ 46 , 64 ]. Regarding the identified families, PLA 2s , as the main venom part, are most active in fraction 15 (PLA 2 , 2.2 µg/mL), in combination with a CTF-II-like disintegrin, against neuroblastoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…The main compound of the fraction 4 is the svMP-i pEKW, while the pEQW containing fraction 7/8 is similarly potent. According to these results, the P. flavoviridis venom, svMP-is, exhibits remarkable effects on SH-SY5Y cells, while, until now, only the correlating svMP of most Protobothrops venoms were known to have an important role in envenomation-related pathologies [ 46 , 64 ]. Regarding the identified families, PLA 2s , as the main venom part, are most active in fraction 15 (PLA 2 , 2.2 µg/mL), in combination with a CTF-II-like disintegrin, against neuroblastoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…The current study revealed that SVMPs exhibit different activities such as hydrolyzing of fibrinogen or fibrin, action of thrombin or inhibition of platelet aggregation [ 35 ]. For example, the P–I class BnP1 from B. neuwiedi venom and the P-III class Jararhagin from Bothrops jararaca venom directly hydrolyze fibrinogen and fibrin [ [36] , [37] , [38] ], HF3 and bothropasin from Bothrops jararaca inhibit platelet aggregation [ 39 ], Mocarhagin isolated from Naja venom inhibits platelet aggregation by cleaving GPIb [ 15 ], Berythractivase from Bothrops erythromelas , which acts as a thrombinogen activator [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main compound of the most active fraction 6 is the svMP-i pENW, while the pEQW containing fraction 7 less cell toxic (4.6 μg/mL). According to this cytotoxicity results, the P. flavoviridis venom svMP-i exhibits remarkable effects on SH-SY5Y cells, while until now only the correlating svMP of most Protobothrops venoms were known for their important role in envenomation-related pathologies [46,60]. Regarding the identified families, PLA2s as main venom part are most active in fractionss 15 (PLA-N(O), 2.2 µg/mL) and 14 (PLA2 BP-I/II, 4.0 µg/mL), against neuroblastoma cells.…”
Section: Bradykinin-potentiating Peptides and Snake Venom Metalloprotmentioning
confidence: 95%